Herramienta en ambiente web para la visualización de las corrientes de viento en Costa Rica - Romero-Lépiz, Johnny Arturo (Instituto Tecnológico de Costa Rica, 2015)
The objective of this work is to develop an application to show the Costa Rica’s vector wind field. Data of wind speed and direction of the year 2014 were used, this information was provided by the Instituto Meteorológico Nacional and collected by twenty weather stations spread around the country. An interpolation algorithm of inverse distance weighted was developed in order to create a vector field as a representation of the country’s wind flow; the data of the stations of the Instituto Meteorológico Nacional were used as initial data and for other sectors of the country, where no stations are found, the interpolation algorithm was used. Finally a web application using HTML, CSS, JavaScript and the D3.js library was developed to show the vector wind field animation, it was performed using lines in motion with the direction and speed of the wind. Keywords: Weather Stations; Inverse distance weighted interpolation; D3.js; Wind power; Climatic zones of Costa Rica; OpenGL; Parallel.js; Geographic Information System.
Web environment tool to display Costa Rica’s wind flow
Informe de Trabajo de Graduación (Licenciatura en Ingeniería en Computadores). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Computadores. 2015.
Keywords: Estaciones Meteoreológicas; Zonas Climáticas; Energía Eólica; Instituto Meteorológico Nacional; Datos: dirección y rapidez del viento